2021
DOI: 10.21608/ejoh.2021.74606.1173
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of Vegetative Growth Criteria and Accumulation of Secondary Metabolites by Using Compost Tea and Paclobutrazol on Henna (Lawsonia inermis L.) Plants

Abstract: A POT experiment was carried out during the two successive seasons of 2018 and 2019 at Beni-Suef governorate, Egypt, to investigate the effect of compost tea and foliar-spray application of paclobutrazol (PBZ) on vegetative growth characteristics and some chemical constituents of henna plants.Obtained results revealed that the best vegetative growth characters (plant height, number of main branches/plant, number of lateral branches/main branches, leaves number per plant, leaves fresh and dry weights/plant), ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…In the same trend, the best values were obtained for leaves fresh and dry weights/plant and photosynthetic pigments of henna plants, due to the use of 60 ml compost tea/l 9 . Regarding the fertile content of compost tea from NPK (Table 2), the application of compost tea improved NPK absorption in plants 9 and reestablished the ionic balance by alleviating excessive absorption levels of Na in sugar beet plants 7 . This tendency supports the obtained results in Table 4.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the same trend, the best values were obtained for leaves fresh and dry weights/plant and photosynthetic pigments of henna plants, due to the use of 60 ml compost tea/l 9 . Regarding the fertile content of compost tea from NPK (Table 2), the application of compost tea improved NPK absorption in plants 9 and reestablished the ionic balance by alleviating excessive absorption levels of Na in sugar beet plants 7 . This tendency supports the obtained results in Table 4.…”
Section: Discussionmentioning
confidence: 99%
“…The obvious increment in potassium and "-amino N content of juice may be attributed to that nutrient analysis revealed that nitrogen and potassium were well presented in compost tea added under this study (Table 2), making teas an interesting source of fertilizer for crop application 33 by increasing the concentration of solute substances other than sucrose and the inter-relationships between the accumulation of sucrose and these so-called impurities, which plays a principal role in the values of the quality index. The increment in sugar yield may be back to the fact that adding compost tea to the soil improved root yield/fed (Table 3), along with the accumulation of dry matter, in turn, enhanced sucrose content in beetroots (Table 4), as well as improved total carbohydrates 9 . The results are consistent with those obtained by Pibars et al 8 and Osman et al 7 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation